2016
DOI: 10.1371/journal.pone.0159033
|View full text |Cite
|
Sign up to set email alerts
|

Sendai Virus Induces Persistent Olfactory Dysfunction in a Murine Model of PVOD via Effects on Apoptosis, Cell Proliferation, and Response to Odorants

Abstract: BackgroundViral infection is a common cause of olfactory dysfunction. The complexities of studying post-viral olfactory loss in humans have impaired further progress in understanding the underlying mechanism. Recently, evidence from clinical studies has implicated Parainfluenza virus 3 as a causal agent. An animal model of post viral olfactory disorders (PVOD) would allow better understanding of disease pathogenesis and represent a major advance in the field.ObjectiveTo develop a mouse model of PVOD by evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 48 publications
2
46
0
1
Order By: Relevance
“…This may account for the prolonged presence of viral protein and viral RNA within the OB. 41,45 Studies demonstrated high neurovirulence of HSV for the CNS. In vivo studies of HSV-1 and HSV-2 consistently showed high degree of neuroinvasion within the olfactory pathway as well as in higher cortical centers, resulting in encephalitis and cell death.…”
Section: Viral Specific Effects On the Olfactory Systemmentioning
confidence: 99%
“…This may account for the prolonged presence of viral protein and viral RNA within the OB. 41,45 Studies demonstrated high neurovirulence of HSV for the CNS. In vivo studies of HSV-1 and HSV-2 consistently showed high degree of neuroinvasion within the olfactory pathway as well as in higher cortical centers, resulting in encephalitis and cell death.…”
Section: Viral Specific Effects On the Olfactory Systemmentioning
confidence: 99%
“…We propose that SARS-CoV-2 might affect the integrity or regeneration/renewal of the olfactory epithelium, impacting the physiological function of olfactory sensory neurons (Figure 2). Hence, we can cite the example of Sendai virus which has been shown to impair olfaction by reducing the regeneration of the olfactory epithelium and olfactory bulb in the mouse [51]. In in vitro experiments on murine olfactory neurons infected with this virus, the number of odorant-responsive cells were decreased.…”
Section: Covid-19 and Reduced Oro-naso-sensory (Ons) Perceptionmentioning
confidence: 99%
“…However, it has been hypothesized that odor detection thresholds represent the function of the peripheral olfactory system to a higher degree than the central nervous processing of olfactory information. Although central nervous damage has also been described, respiratory viruses are expected to produce major damage at the level of the olfactory epithelium [ 6 , 7 ]. Hence, evaluating detection thresholds may provide specific information on the olfactory loss due to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%